El rol de los padres de familia en la formación académica de los estudiantes de la Unidad Educativa “Hispanoamérica”, Riobamba. - Bernardi Arévalo, Cristhián Sebastián (2024)
The main objective of this research study was to determine the relationship between the role of parents and parental styles in the academic formation of students at the “Hispanoamérica” Educational Unit, Riobamba; The roles of the parents will depend on whether it is the mother or the father, both have different roles where the father is the protective figure and the mother is the being who is closer to accompany us through our life journey, but both together fulfill certain roles with the child, in turn the roles of parents will vary depending on the parental style of the child, since there are 4 parental styles (authoritarian, democratic, permissive and negligent). The methodology used corresponds to a quantitative approach, with a non-experimental design, the type of research is descriptive because of its scope; because of the objective it is basic; because of the place it is field research; because of the time of the study it is transversal. The population consisted of the “Hispanoamérica” Educational Unit and its sample was non-probabilistic and intentional, consisting of 62 students corresponding to eighth, ninth and tenth grades of EGB. The survey technique was used with its respective instrument, the questionnaire of parental roles and the questionnaire of the characteristics of parental styles. The interpretation of the data was carried out by means of the Excel program, where the elaboration of statisticians was carried out which was tables and pies of the analysis of each dimension that was indicated in the questionnaires, obtaining results of global form according to the 62 students of the Educational Unit “Hispanoamérica” about the roles of the parents and the parental styles; where it is concluded that the most predominant roles for the parents is the feeding with 96. 78%, health with 90.33%, clothing with 90.32%, protection and security also with 90.32%, education with 87.10% and economic contribution with 85.48%. Also the most predominant parental styles are democratic and permissive, with a very low percentage of authoritarian and negligent styles.